The Effect of Cardamom Aromatherapy on the Frequency of Nausea and Vomiting in First Trimester Pregnant Women at the Wondiboi Community Health Center - Suartini, Suartini (Jurusan Kebidanan Poltekkes Kemenkes Sorong, 2024)
Management of nausea and vomiting in pregnancy consists of pharmacological and non-pharmacological. The type of research is quasi experimental research, namely research that tests interventions on a group of subjects, with a research design using a one group pre test-post test design. The results of the study showed that the mean value of the frequency of nausea and vomiting in respondents showed a decrease, which means that based on the score value on the PUQE 24 questionnaire, there was a decrease in the frequency of nausea and vomiting in respondents, where based on the mean value of the frequency of nausea and vomiting before being given intervention, the average respondent had a frequency of nausea and vomiting at a moderate level. However, after being given the intervention, the respondent's frequency of nausea and vomiting decreased to the level of mild nausea and vomiting. Conclusion: Cardamom aromatherapy has an effect on the frequency of nausea and vomiting of pregnant women at the Wondiboi Community Health Center.